Častnoe neoficial'noe pis'mo i teksty-rassuždenija. Persoenlicher Briefwechsel und Eroerterungen auf Russisch Ein Lehr- und Uebungsheft fuer Fortgeschrittene. Studienhilfen, Band 5 - Oppermann, Hans (Slavistische Beitraege, 1997)
The purpose of the present exercise book is to expand the ability to write letters using authentic text examples and to deepen it through a rich exercise system. Special emphasis is placed on the teaching of linguistic variants in order to enrich the expressiveness.